Immunity to the microbiota promotes sensory neuron regeneration - Enamorado, Michel; Kulalert, Warakorn; Han, Seong-Ji; Rao, Indira; Delaleu, Jérémie; Link, Verena M; Yong, Daniel; Smelkinson, Margery; Gil, Louis; Nakajima, Saeko; Linehan, Jonathan L; Bouladoux, Nicolas; et al. (Cell, 2023)
Tissue immunity and responses to injury depend on the coordinated action and communication among physiological systems. Here, we show that, upon injury, adaptive responses to the microbiota directly promote sensory neuron regeneration. At homeostasis, tissue-resident commensal-specific T cells colocalize with sensory nerve fibers within the dermis, express a transcriptional program associated with neuronal interaction and repair, and promote axon growth and local nerve regeneration following injury. Mechanistically, our data reveal that the cytokine interleukin-17A (IL-17A) released by commensal-specific Th17 cells upon injury directly signals to sensory neurons via IL-17 receptor A, the transcription of which is specifically upregulated in injured neurons. Collectively, our work reveals that in the context of tissue damage, preemptive immunity to the microbiota can rapidly bridge biological systems by directly promoting neuronal repair, while also identifying IL-17A as a major determinant of this fundamental process.
Published by Elsevier Inc.
Keywords: Axons; Interleukin-17; Microbiota; Nerve Regeneration/physiology; Sensory Receptor Cells; Animals; Mice; Th17 Cells/cytology